Evaluation of surface properties of betung bamboo (Dendrocalmus asper) strands under various heat treatment duration and temperature - Risa Nurin Baiti; Sena Maulana; Wahyu Solafide Sipahutar; Rio Ardiansyah Murda; Fajar Aditya Julyatmojo; Astri Aulia Suwanda; Muhammad Saeful Fadlan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
The abundance, rapid growth characteristics and good mechanical properties have made betung bamboo as good alternative materials to replace the slow growing wood. To adress the susceptibility to insects and water attack, the making of bamboo composites, using resin as matrix, has been widely practiced. Thus, the surface properties of bamboo strands are crucial to determine the optimum interaction with resin. This study evaluate the effect of heat treatment to improve the surface properties of bamboo strands, such as the wettability and the color change. Beforehand, the freshly cut bamboo was cut, cleaned and sand-grinded. The heat treatment was done at 140o and 160oC for 1, 2, and 3 hours. After cooling down to room temperature, the contact angle of bamboo’s surface was measured by sessile drop methode. The wettability was indicated by constant of contact angle change rate, K. Besides, the change of color was also determined. After the experiments, it was obtained that the bamboo surface tends to be more hydrophobic and has darker color with longer duration of heat treatment. Higher temperature and longer duration of heat treatment can cause more evaporation of liquid inside bamboo and decrease hydrophilicity of the surface.